Sub-1 V low power wide range injection-locked frequency divider - Yu, Xiao Peng (2009)
In this letter, the sub-1 V low power, wide range operation of an injection-locked frequency divider with a common-gate configuration is presented. The performances in terms of locking range and power consumption have been improved in the sub-1 V low supply voltage. Two set of prototypes, performing divide-by-2 and divide-by-3, have been fabricated in CSM 0.18 um CMOS process to verify the proposed designs. In the proposed units, a locking range of 40% has been achieved with a power consumption of 0.24 mW in the 0.8 V supply voltage. The operating range of 2.2 GHz to 5.2 GHz has been achieved with a power consumption of 1.1 mW for a 1.5 V supply voltage.